Role of the shariah advisory council (sac) in dispute resolution process: perspective on recent case development - Mustaffa, Aminuddin; Moharani, Siti Nurul Aziera
The Central Bank of Malaysia Act 2009 ('CBA 2009') has granted the authority to the Central Bank of Malaysia for the establishment of the Shariah Advisory Council ('SAC') as the highest and sole authority to be referred by civil courts in dealing with Islamic banking, takaful and Islamic finance cases in Malaysia. This newly introduced Act has repealed the previous Central Bank of Malaysia Act 1958. By virtue of this newly introduced statute, the SAC has been accorded with the role as a sole Shariah authority in Islamic finance. While the rulings of the SAC shall prevail over any contradictory ruling given by a Shariah body or committee constituted in Malaysia, the court and arbitrator are also required to refer to the rulings of the SAC for any proceeding relating to Islamic financial business and such ruling shall be binding. At a glance, it seems that the new CBA 2009 has conferred a vital role and power to the SAC. The Act suggests that it is mandatory for the court to refer to the SAC in resolving a legal dispute, particularly on issues involving Islamic banking and finance under Malaysian law. However, in practice, the impact of this newly introduced Act remains debatable. This paper aims to focus on the effectiveness of the role and power of the SAC, specifically in legal dispute-resolution process pertaining to Islamic banking and finance matters under Malaysian law. Furthermore, this paper will study to what extent the amendment has enhanced the role and power of the SAC in the dispute resolution process under Malaysian law, and last but not least, it will analyse to what extent the Malaysian courts are bound to refer disputes involving Shariah issues in Islamic banking and finance to the SAC